Detection and molecular characterization of leishmania in dogs from northeastern Brazil - Evaristo, Anna Maria; Silva , Ivo Wesley; Oliveira, Glauber Meneses; Silva, Ryan Emiliano; Costa, Jaciara; Veschi, Josir Laine Aparecida; Marcili , Arlei; Horta, Mauricio (Brazilian Journal of Global Health, 2021)
OBJETIVO: O objetivo do presente estudo foi determinar a soroprevalência atual da Leishmaniose Visceral Canina (LVC) em cães domiciliados, os fatores associados à soropositividade, espécies circulantes de Leishmania e análise espacial em seis municípios das mesorregiões do Sertão e São Francisco, localizados no estado de Pernambuco, Brasil. MÉTODOS: Amostras de sangue de 330 cães foram analisadas por meio de ensaios sorológicos e moleculares: teste rápido imunocromatográfico (DPP®); ensaio imunoenzimático (ELISA), teste de imunofluorescência indireta (IFAT) e reação em cadeia da polimerase (PCR). As sequências de nucleotídeos de quatro marcadores gênicos (kDNA, catepsina L-like, SSU-rDNA e gGAPDH) foram exploradas para realizar uma análise filogenética. RESULTADOS: A soroprevalência geral foi de 13% (43/330) em cães simultaneamente positivos no DPP®, ELISA e IFAT, sendo 13,9% (23/165) no Sertão e 12,1% (20/165) no São Francisco. Os fatores associados à alta prevalência de anticorpos de L. infantum em cães foram morar no município de Petrolina (P = 0,045) e apresentar lesões oculares (P = 0,049) (P ≤ 0,05). Aglomerados significativos de cães positivos foram encontrados em áreas rurais. Os valores de positividade obtidos por PCR com base nos genes kDNA e catepsina L-like foram 6,7% (22/330) e 2,4% (8/330), respectivamente. Na análise filogenética, observou-se que todos os isolados obtidos apresentaram 100% de similaridade com Leishmania infantum. CONCLUSÕES: Pela primeira vez, L. infantum foi confirmado como o agente etiológico da LVC nesta região. Assim, a avaliação da estrutura genética de populações de Leishmania spp. é importante para compreender os padrões de transmissão de LVC. DESCRITORES: Leishmaniose canina, Diagnóstico, Geoprocessamento, Filogenia. ABSTRACT OBJECTIVE: The aim of the present study was to determine the current seroprevalence of canine leishmaniasis (CanL) among domiciled dogs, factors associated with seropositivity, circulating Leishmania species and spatial analysis, in six municipalities in the Sertão and São Francisco mesoregions, which are located in the state of Pernambuco, Brazil. METHODS: Blood samples from 330 dogs were analyzed using serological and molecular assays: dual path platform (DPP®); enzyme-linked immunosorbent assay (ELISA), indirect fluorescent antibody test (IFAT) and polymerase chain reaction (PCR). The nucleotide sequences of four gene markers (kDNA, cathepsin L-like, SSU-rDNA and gGAPDH) were explored to perform a phylogenetic analysis. RESULTS: The overall seroprevalence was 13% (43/330) in dogs that were simultaneously positive according to DPP® ELISA and IFAT, consisting of 13.9% (23/165) in Sertão and 12.1% (20/165) in São Francisco. The factors associated with high prevalence of L. infantum antibodies in dogs comprised living in the municipality of Petrolina (P = 0.045) and presenting ocular lesions (P = 0.049) (P ≤ 0.05). Significant clusters of positive dogs were found in rural areas. The positivity values obtained through PCR based on the genes kDNA and cathepsin L-like were 6.7% (22/330) and 2.4% (8/330), respectively. In the phylogenetic analysis, it was observed that all the isolates obtained showed 100% similarity to Leishmania infantum. CONCLUSION: For the first time, L. infantum was confirmed as the etiological agent of CanL in this region. Thus, assessment of the genetic structure of populations of Leishmania spp. is important for understanding the patterns for transmission of CanL. DESCRIPTORS: Canine leishmaniasis, Diagnosis, Geoprocessing, Phylogeny.